Exploring the possibilities of PAR and communicative competence in curricular negotiations in Costa Rican English learning courses - Cano Morales, Rodrigo (2021)
Exploring Participatory Action Research and communicative competence in democratic education and curricular negotiations allow delving into social dynamics, reflection and communication in the target language. As a result, this paper merges theoretical references and the experience acquired through the modules and products obtained when fostering communicative competence and curricular negotiations in my teaching-learning praxis. Since participation and documentation of the experience reflect on the instruments, contexts, and various dynamics in the classroom reality, communicative competence and PAR relate to the background and classroom dynamics, guiding learners and teachers to dialogic and democratic education. Therefore, these processes of constantly integrating needs, contexts, backgrounds, and curriculum present a series of options in the classroom to foster communication and to tailor language learning realities in the class, sharing insights on contexts and requirements when learning a language.